2014
DOI: 10.1039/c4ob00382a
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent probe for intracellular cysteine overcoming the interference by glutathione

Abstract: Cysteine (Cys) plays important roles in many physiological processes of eukaryotic cells and its detection in cells is of fundamental significance. However, glutathione (GSH), homocysteine, N-acetyl-L-cysteine and other thiols greatly hamper the detection of Cys. In particular, GSH strongly interferes with the detection of cellular Cys (30–200 μM) due to its high intracellular concentration (1–10 mM). In this work, an off–on fluorescent probe (HOTA) for the detection of Cys is presented. This probe possesses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…22 Although reversible, the dissociation of the 2-FPBA-cysteine adduct only occurs over the course of hours. The cysteine reactivity of 2-FPBA might interfere with its conjugation with semicarbazide.…”
Section: Resultsmentioning
confidence: 99%
“…22 Although reversible, the dissociation of the 2-FPBA-cysteine adduct only occurs over the course of hours. The cysteine reactivity of 2-FPBA might interfere with its conjugation with semicarbazide.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the aortic ring was treated with vehicle (20 min); thereafter, cumulative increasing concentrations of NA, evoking concentration-dependent vasoconstriction, were added again. In the lower panel, complete recovery of the vasoconstriction effects of NA is evident useful feature of a "smart" H 2 S donor (Calderone, Martelli, Testai, Citi, & Breschi, 2016), as it would ensure that the release of H 2 S does not occur spontaneously and in an undifferentiated way but is particularly facilitated in just the cell cytosol, where the highest concentrations of organic thiols are present: GSH (in 1-10 mM range) and cysteine (in 30-200 μM range; Tian et al, 2014) In this context, we have previously demonstrated that erucin, a natural isothiocyanate, typically present in many edible cruciferous plants, behaved as a smart H 2 S donor, since it exhibited slow, longlasting, and thiol-dependent release of H 2 S; however, this result was obtained in a "cell-free" experimental model in vitro . Therefore, the first objective of this work was to test the ability of erucin to enter vascular smooth muscle cells and promote the generation of H 2 S using the intracellular pool of organic thiols.…”
Section: Discussionmentioning
confidence: 99%
“…We first determined the absorbance and emission profile of compound 1 (Figures S1 and S2 in Appendix S1, Supporting Information) in the presence of varying concentrations of Cys, Hcy, and GSH in HEPES buffer (pH 7.24). We tested from 5 to 200 μM for Cys and Hcy, and 5 μM to 10 mM for GSH based on their intracellular concentrations . As demonstrated in Figure (a)–(c), the fluorescence emission signal of 1 at 544 nm (λ ex.…”
Section: Acknowledgmentsmentioning
confidence: 82%